DUKUNGAN KELUARGA DENGAN SELF MANAGEMENT PADA PENDERITA DIABETES MELLITUS TIPE II - Eltrikanawati, T; Oktavia, Nia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Diabetes Mellitus is a medical condition in the form of an increase in blood glucose levels exceeding the normal limit. When blood glucose levels increase, activities become limitied and difficulties in doing self care or self management so that it can worsen the health status. One of the factors that affect self-management in patients with Diabetes Mellitus Type II is family. The purpose of this study is to find out the Relationship between Family Support and Self Management in Diabetes Mellitus Type II Patients. Using quantitative research with analytical design with a crosssectional approach to 66 patients with type II diabetes mellitus in the working area of the Sei Langkai Health Center in Batam City. The implementation time is July 26 to August 8, 2024. Sampling using purposive sampling technique. The measurement tool in this study uses a questionnaire. The data analysis used is the spearman correlation test. The result of the spearman test obtained the value of r = 0,915 with p value 0,000 < 0,05 which means H0 is rejected and Ha is accepted. So it can be concluded that there is a strong relationship and significance between Family Support and Self Management in Diabetes Mellitus Type II Patients in the Working Area of the Sei Langkai Health Center in Batam City in 2024. It is hoped that research of can be useful as a basis for Type II Diabetes Mellitus sufferers to improve their self management to avoid complications.Keywords: Type II Diabetes Mellitus, Self Management, Family Support.